Subproteomes of soluble and structure-bound Helicobacter pylori proteins analyzed by two-dimensional gel electrophoresis and mass spectrometry - Backert, Steffen; Kwok, Terry; Schmid, Monika; Seibach, Matthias; Moese, Stefan; Peek, Richard M.; König, Wolfgang; Meyer, Thomas F.; Jungblut, Peter R. (Proteomics, 2005)
Helicobacter pylori is one of the most common bacterial pathogens and causes a variety of diseases, such as peptic ulcer or gastric cancer. Despite intensive study of this human pathogen in the last decades, knowledge about its membrane proteins and, in particular, those which are putative components of the type IV secretion system encoded by the cag pathogenicity island (PAI) remains limited. Our aim is to establish a dynamic two-dimensional electrophoresis- polyacrylamide gel electrophoresis (2-DE-PAGE) database with multiple subproteomes of H. pylori (http://www.mpiib-berlin.mpg.de/2D-PAGE) which facilitates identification of bacterial proteins important in pathogen-host interactions. Using a proteomic approach, we investigated the protein composition of two H. pylori fractions: soluble proteins and structure-bound proteins (including membrane proteins). Both fractions differed markedly in the overall protein composition as determined by 2-DE. The 50 most abundant protein spots in each fraction were identified by peptide mass fingerprinting. We detected four cag PAI proteins, numerous outer membrane proteins (OMPs), the vacuolating cytotoxin VacA, other potential virulence factors, and few ribosomal proteins in the structure-bound fraction. In contrast, catalase (KatA), γ-glutamyltranspeptidase (Ggt), and the neutrophil-activating protein NapA were found almost exclusively in the soluble protein fraction. The results presented here are an important complement to genome sequence data, and the established 2-D PAGE maps provide a basis for comparative studies of the H. pylori proteome. Such subproteomes in the public domain will be effective instruments for identifying new virulence factors and antigens of potential diagnostic and/or curative value against infections with this important pathogen. © 2005 WILEY-VCH Verlag GmbH & Co. KGaA.
Created from Fastlane, Scopus look-up
Keywords: Mass spectrometry; Molecular pathogenesis; Pathogenicity island; Two-dimensional gel electrophoresis; Type IV secretion; Virulence